2009
DOI: 10.1111/j.1365-2524.2009.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Silenced voices: hearing the stories of parents bereaved through the suicide death of a young adult child

Abstract: The current paper reports findings from a qualitative research project that aimed to explore parents' experiences following the suicide death of their young adult child. Twenty-two Australian parents told of the suicide death of their son or daughter during the data collection period (2003 to late 2004). One narrative theme drawn from the interview data is reported here: the way in which suicide-bereaved parents feel unable to talk about their child's life and death, their experience of suicide and their resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 33 publications
6
64
0
2
Order By: Relevance
“…Therefore strategies to support and understand those affected are integral to suicide prevention. In providing appropriate care to survivors it is crucial that health professionals acknowledge that grief experienced after suicide may be more intense, complex, and prolonged than grief due to other losses (Cvinar, 2005;Jordan, 2008;Maple, Edwards, Plummer, & Minichiello, 2010). Also, due to the exceptionally traumatic and stigmatising nature of suicide, communication between the bereaved and service providers may be laden with tension, resulting in less than optimal relationships (Botha, Guilfoyle, & Botha, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore strategies to support and understand those affected are integral to suicide prevention. In providing appropriate care to survivors it is crucial that health professionals acknowledge that grief experienced after suicide may be more intense, complex, and prolonged than grief due to other losses (Cvinar, 2005;Jordan, 2008;Maple, Edwards, Plummer, & Minichiello, 2010). Also, due to the exceptionally traumatic and stigmatising nature of suicide, communication between the bereaved and service providers may be laden with tension, resulting in less than optimal relationships (Botha, Guilfoyle, & Botha, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of suicide survivors being understood and accepted is emphasized in previous research that has found that they experience greater levels of societal rejection than those bereaved by other causes of death, which further complicates their grief (Cvinar, 2005;Maple, Edwards, Plummer, & Minichiello, 2010;Sveen & Walby, 2008). Resonating with a study by McMenamy, Jordan, and Mitchell (2008), participants of the Quilt project described feeling connected with others and appreciated the opportunity to share the stories of their loved ones in a nonjudgmental environment.…”
Section: Discussionmentioning
confidence: 99%
“…Kiek vėliau moteris kalba apie baimes, kylančias galvojant apie socialines sąveikas ("<…> aš net bijodavau į parduotuvę išeit, kad jie visi mato, kad taip atsitiko" (7:63)). Kiti tyrimai taip pat rodo, kad neigiamos nuostatos nusižudžiusiųjų artimųjų atžvilgiu gali dar labiau padidinti jų kaltės išgyvenimus, pabloginti savijautą (Minamizono, Motohashi, Yamaji, & Kaneko, 2008;Maple et al, 2010). Tyrimo dalyvių pasakojimuose minimos ir aplinkinių apkalbos, savižudybės priežasčių ieškojimas, kaltinimas.…”
Section: Stigmatizuojančios Aplinkinių Reakcijosunclassified